Evaluating the efficiency of educational services in Al-Dabouni district in Wasit - Ali Ahmed, Hussein; Hashim Sahan, Abbas (Journal of Planner and Development, 2024)
Abstract: Every human being has the right to education, and the state is legally obligated to provide it to its people. From this standpoint, the educational service is one of the services governed and supervised by the state. This educational service meets the needs of the times by preparing graduates to engage in life activities on all social and economic dimensions.This research shed light on the study of evaluating the efficiency of educational services in Al-Dabouni district in Wasit Governorate and analyzing their efficiency in comparison with Iraqi standards. The evaluation shows insufficient school buildings in the district, and the research suggests building a sufficient number of educational buildings to fill the current deficit. It is also recommended to improve and develop existing schools and use modern technology in education. The summary is based on previous studies on the efficiency of educational services and an analysis of local planning standards.